Essence and methods of the assessment of competitiveness of firm (Journal of Economic Research & Business Administration, 2016)
High competitiveness of firm is the guarantor of receiving high profit in market conditions. Thus the firm aims to reach such level of competitive-ness which would help it to survive on rather long-term time span. In this regard before any organization there is a problem of strategic and tactical management of development of ability of the enterprise to survive in the changing market conditions. In article theoretical questions of essence and methods of an assessment of competitiveness of firm reveal. The author considered characteristics of competitiveness the enterprise, the purpose of development and creation of competitiveness of firms. Today there is a number of techniques of an assessment of competitiveness. Short charac-teristics of the main methods of an assessment of competitiveness of the enterprises are provided in article. The purpose of development and cre-ation of model of competitiveness of firms usually consists in need of the correct definition of competitive strategy. As a rule, it is necessary to apply some methods of determination of competitiveness of firm to an effective assessment at once. The most effective and widespread is the complex analysis of competitiveness
Keywords: competitiveness; strategy of firm; strategic programs; com-petitiveness assessment; internal environment of firm; competitive advan-tages.